Base-mediated [2 + 4] cycloadditions of in situ formed azaoxyallyl cations with N-(2-chloromethyl)aryl amides. Issue 40 (1st October 2018) - Jin, Qiaomei; Gao, Meng; Zhang, Dongjian; Jiang, Cuihua; Yao, Nan; Zhang, Jian
Abstract : A base-mediated [2 + 4] annulation of in situ formed azaoxyallyl cations with in situ generated aza- o QMs has been realized. Abstract : A base-mediated [2 + 4] annulation of in situ formed azaoxyallyl cations with in situ generated aza- o QMs has been realized. This one-pot cycloaddition process assembled the corresponding 1, 4-dihydro-2 H -benzo[ d ][1, 3]oxazines in moderate to good yields (up to 99% yield).